An investigation into the colloidal stability of graphene oxide nano-layers in alite paste. (September 2017) - Ghazizadeh, S.; Duffour, P.; Skipper, N.T.; Billing, M.; Bai, Y.
Abstract: Recent studies have reported that graphene oxide (GO) is capable of enhancing the mechanical properties of hardened Portland cement (PC) pastes. The mechanisms proposed so far to explain this strengthening generally assume that GO is well dispersed in the pore solution of PC paste, serving as a reinforcing agent or nucleation-growth site during hydration. This paper investigates (i) the effect of GO on the hydration of alite, the main constituent of PC cement, using isothermal calorimetry and boundary nucleation-growth modelling, and (ii) the factors controlling the colloidal stability of GO in alite paste environment. Results indicate that GO accelerates the hydration of alite only marginally, and that GO is susceptible to aggregation in alite paste. This instability is due to (i) a pH-dependent interaction between GO and calcium cations in the pore solution of alite paste, and (ii) a significant reduction of GO functional groups at high pH.